2013
DOI: 10.1523/jneurosci.5587-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Modulates Risk-Taking as a Function of Baseline Sensation-Seeking Trait

Abstract: Trait sensation-seeking, defined as a need for varied, complex, and intense sensations, represents a relatively underexplored hedonic drive in human behavioral neuroscience research. It is related to increased risk for a range of behaviors including substance use, gambling, and risky sexual practice. Individual differences in self-reported sensation-seeking have been linked to brain dopamine function, particularly at D2-like receptors, but so far no causal evidence exists for a role of dopamine in sensation-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
0
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 40 publications
5
56
0
8
Order By: Relevance
“…Low doses of D2 agonists reduce dopamine signalling by targeting pre-synaptic autoreceptors, diminishing phasic dopamine bursts and consequently decreasing reward learning and increasing relative learning from punishment [30][31][32][33] . Other studies have shown that low doses of cabergoline increase error awareness and response inhibition 51 , and cause a shift to a more conservative risk taking strategy 52 , all possibly due to a relative shift in indirect over direct pathway functioning. In the absence of nearly any other behavioural or EEG alteration, cabergoline caused a strong behavioural bias for C4B.…”
Section: Discussionmentioning
confidence: 98%
“…Low doses of D2 agonists reduce dopamine signalling by targeting pre-synaptic autoreceptors, diminishing phasic dopamine bursts and consequently decreasing reward learning and increasing relative learning from punishment [30][31][32][33] . Other studies have shown that low doses of cabergoline increase error awareness and response inhibition 51 , and cause a shift to a more conservative risk taking strategy 52 , all possibly due to a relative shift in indirect over direct pathway functioning. In the absence of nearly any other behavioural or EEG alteration, cabergoline caused a strong behavioural bias for C4B.…”
Section: Discussionmentioning
confidence: 98%
“…For example, inactivation of the PFC and/or administration of D2-agonists boosts reward expectancy, lowers punishment sensitivity, impairs behavioral flexibility, and increases risktaking (Kuryloa and Sarah Tanguay, 2003;Goto and Grace, 2005;Norbury et al, 2013). Therefore, when taken to extremes, tonic DA hyperactivity in limbic structures can dampen the influence of PFC-driven feedback on ongoing behavior and thereby result in a hyperfocus towards rewards, impetuous risk-taking, and impaired response modulation, which is characteristic of disinhibited forms of psychopathy Newman and Lorenz, 2004).…”
Section: Population Activity/phasic Da Responses To Reinforcement-prementioning
confidence: 99%
“…First, it is remarkably consistent with a recent study that used a similar paradigm and similar drug (amisulpride), and showed that the selective blockade of D 2 /D 3 receptor with amisulpride led to a similar decrease in probability distortion during risky decision-making (Burke et al, 2017). In another study, Norbury et al (2013) showed that, in low sensation-seeking participants, the dopamine D 2 /D 3 receptor agonist cabergoline increased risk-taking for high winning probabilities, while decreasing it for low winning probabilities. Similarly, Stopper et al (2013) have shown that the administration of a dopamine D 1 receptor agonist increased risk-taking behavior of rats in the context of high winning probabilities but decreased it in the context of low winning probabilities.…”
Section: Discussionmentioning
confidence: 97%